Extended levobunolol release from Eudragit nanoparticle-laden contact lenses for glaucoma therapy - Navneet Kumar; Rohan Aggarwal; Meenakshi K. Chauhan (SpringerOpen, 2020)
Abstract Background Majorly, the reason for the permanent loss of vision is glaucoma. But the currently available common treatment methodologies such as eye drops have various disadvantages like patient incompliance due to repeated administration and poor (1-5%) bioavailability leading to poor efficiency. The objective of this research was to formulate Eudragit-based nanoparticles of levobunolol incorporated into a contact lens to obtain sustained ocular delivery of levobunolol at the therapeutics level. Eudragit nanoparticles of levobunolol were formulated by nanoprecipitation methodology utilizing different ratios of Eudragit S100 and polyvinyl alcohol. The prepared nanoparticles were evaluated and optimized by efficiency of entrapment, particle size, morphology of surface and zeta potential. The optimized nanoparticles were then entrapped into the matrix of the contact lens by the soaking method which were then characterized and compared for optical clarity study, equilibrium swelling study, shelf life and in vitro drug release in simulated tear fluid followed by ex vivo transcorneal permeation study. Results Formulation F3 was obtained as optimized nanoparticle formulation with 102.61 nm ± 3.92 of particle size, − 22.2 mV ± 2.76 of zeta potential and 86.995% ± 1.902 of efficiency of entrapment. The equilibrium swelling index and transmittance of nanoparticle incorporated into contact lenses showed better results when compared to drug solution-loaded lenses. In vitro release indicated more sustained drug profiles (84.33% ± 0.34 of drug release over a period of 12 days) as compared to drug solution-loaded lenses (89.282% ± 0.900 of drug release over a period of 3 days). Ex vivo transcorneal permeation studies showed more permeation (6.75% ± 0.170) through contact lenses as compared to marketed eye drops (3.03% ± 0.088). Conclusion This research demonstrates the remarkable results of drug-laden contact lenses to serve as a great medium for the continued delivery of ocular drugs without affecting the physical and optical characteristics of the lens content.